Efektivitas Media E-Book untuk Meningkatkan Motivasi dan Penguasaan Konsep Siswa - Putri Wulandari Nabila; Ratu Betta Rudibyani; Emmawaty Sofya (Universitas Lampung, 2019)
This research aims to describe the effectiveness of e-book to increase motivation and students’ concepts mastery in the acid-base titration topic. The research method used is quasi-experimental with pretest-posttest control group design. The increasing motivation and students’ concept mastery is measured by the average value of n-Gain learning motivation and students’ concept mastery after learning using an e-book. The results of the hypothesis test showed that there are significant differences between n-Gain’s average value of learning motivation and students’ concepts mastery e-book usage and non-e-book usage. Learning motivation and students’ concepts mastery of acid-base titration had a